Ultrasound-guided single shot preemptive erector spinae plane block for thoracic surgery in a pediatric patient - Çiftçi, Bahadır; Ekinci, Mürsel (Kare Publishing, 2020)
The ultrasound-guided erector spinae plane block (ESPB) is a novel interfascial plane block that provides thoracic analgesia at T5 level. ESPB is easy to perform and it is safe due to USG guidance.[1] Thus, ESPB may be a good alternative to other invasive techniques, such as thoracal epidural analgesia in the postoperative analgesia treatment following thoracic surgery. In this correspondence, our aim is to present our effective ESPB experience for a pediatric patient.
Pediatrik hastada preemtif erector spina plan bloğunun toraks cerrahisi sonrası analjezik etkinliği
Keywords: Erector Spinae Plan Block; Thoracic Surgery; Pediatric; Erektor Spina Plan Bloğu; Göğüs Cerrahisi; Pediatri